Scale up of anaesthesia services in underserved rural Tanzania - E. Kweyamba; AS Nyamtema; JC LeBlanc; A. Shayo; RB George; H. Scott; O. Kilume; J. Bulemela; Z. Abel; G. Mtey (BMC, 2023)
Abstract Background Because of critical shortage of physician anaesthesiologists, the government of Tanzania adopted a task shifting strategy for provision of anaesthesia services. This paper describes the results of an operational study designed to increase the number of anaesthesia providers for emergency obstetric surgeries in order to reduce maternal and perinatal mortality in underserved rural Tanzania. Methods In 2016 a before-after cohort study was conducted in seven health centres in rural Tanzania. Five health centres received an intervention and two were selected to track secular trends (control group). Ten associate clinicians, i.e. assistant medical officers, clinical officers, and nurse midwives, from five health centres were trained in anaesthesia skills for emergency obstetric surgeries for three months followed by quarterly supportive supervision, mentoring and teleconsultation to reinforce skills. Primary and secondary outcome measures included Caesarean delivery (CD) rate, quality and safety of anaesthesia, and uptake of the educational program for anaesthesia. Results Out of the 2,179 CDs performed in the intervention facilities from 2016 to 2019, two women died from complications of anaesthesia. The risk of death from anaesthetic complications was 0.9 per 1000 CD (95% CI 0.1-3.3. The risk of death was not established in the control group because of inadequate documentation and records keeping. The proportion of CD performed under spinal anaesthesia in intervention facilities doubled from 28% (60/214 with 95% CI 22-35) at baseline (July 2014 - June 2016) to 57% (558/971 with 95% CI of 54-61) in year three (July 2018 - June 2019), while in the control group increased by only 40% from 19% (92/475 with 95% CI of 16-23) at baseline and 27% (68/251 with 95% CI of 22-33) in year three. In 2020I, this educational training program was then adopted by the government with minor content changes and increasing duration of training to six months. Conclusions This three month educational training program for associate clinicians in anaesthesia, complemented by supportive supervision, can increase the CD rate to one that fills the "unmet need" and the proportion of operations performed under spinal anaesthesia, the gold standard technique for CD. The program can be used to meet the urgent demand for anaesthesia services in other underserved areas in Africa.